BILATERAL GIANT MUCINOUS CYSTADINOCARCINOMA OF THE OVARY: A CASE REPORT AND MANAGEMENT OPTIONS IN LIBERIA - Rabiu A (Ntec Specialist, 2019)
Background:Ovarian cancer is ranked the second most common gynecological cancer in developing countries and constitutes the fourth most common of all cancers in women. Unlike other female genital cancers, ovarian cancer has no signature symptoms or signs, and thus lacks reliable screening modalities that limit the opportunity for an early diagnosis and treatment. Case Presentation: Here, we detail the case of a 44-year-old multipara who presented with complaints of rapidly progressing abdominal swelling of 6 months' duration. The swelling was associated with abdominal pains, dyspepsia, belching, early satiety, nausea, constipation and scanty menses. An early ultrasound revealed bilateral ovarian cysts both measuring less than 2 cm. On examination, she was acutely ill looking, alert and oriented, afebrile, not pale, anicteric, and had no pedal edema. The abdomen was grossly distended. There was mild generalized tenderness. Abdominal masses were not easily discernible due to marked distension and tenderness. Abdomino-pelvic ultrasound revealed a huge abdomino-pelvic multi-septated cystic mass with complex echo pattern and free intraperitoneal fluid. A CA125 assay done showed markedly elevated value (160 U/ml). An assessment of advanced ovarian tumor was made. She was prepared and planned for exploratory laparotomy surgical staging and optimum surgery. She had total abdominal hysterectomy (TAH), bilateral salpingooophorectomy (BSO) complete omentectomy and adjuvant chemotherapy. Conclusion: Mucinous cystadenocarcinoma of the ovary is rare among epithelial tumors. Its management is quite challenging especially in developing countries due to late presentation and lack of available diagnostic and follow up screening tools